Macrophage-specific IRF5 deficiency stabilizes atherosclerotic plaques in ApoE−/− mice. (25th November 2020) - Hilgendorf, I; Haerdtner, C; Leipner, J; Dufner, B; Hoppe, N; Wolf, D; Stachon, P; Zirlik, A; Bode, C
Abstract: Background: Interferon regulatory factor (IRF) 5 is a transcription factor promoting inflammatory macrophage polarization (M1 type). Given the central role of macrophages in atherosclerotic plaque development we hypothesized that macrophage specific deletion of IRF5 will protect from atherosclerosis. Purpose: Investigate whether intrinsic blockade of M1 macrophage polarization ameliorates atherosclerosis Methods: Female ApoE−/−LysMCre/wtIRF5flox/floxand ApoE−/−LysMwt/wtIRF5flox/floxmice were fed a high cholesterol diet for 3 months, and atherosclerotic plaque size and compositions as well as inflammatory gene expression were analyzed. Mechanistically, IRF5-dependend bone marrow derived macrophage cytokine profiles were tested under M1 and M2 polarizing conditions. Aortic macrophage chimerism in irradiated ApoE−/− mice reconstituted with a mixture of CD45.1+ ApoE−/− (WT) and CD45.2+ ApoE−/− LysMCre/WtIRF5flox/flox(KO) bone marrow was evaluated to distinguish systemic from intra-plaque effects on monocyte/macrophage kinetics. Results: Macrophage-specific IRF5 deficiency blunted LPS/IFNg-induced IL-1β and TNFα gene expression in vitro. In ApoE−/− mice, macrophage-specific IRF5 deficiency did not alter lesion size in the aortic root but significantly reduced macrophage and lipid contents by about 25% while increasing collagen deposition by over 30%. This was accompanied by relative reductions in gene expressions of pro-inflammatory (IL-1β, IL-6, IL-12) and increases in anti-inflammatory (Mertk, TGFβ, CD206) markers in atherosclerotic aortas of ApoE−/−LysMCre/wtIRF5flox/floxmice. When competing with IRF5 deficient cells in mixed irradiation bone marrow chimeras, IRF5 competent macrophages showed an advantage in accumulating in atherosclerotic aortas as disease progressed independent of monocyte recruitment. Conclusion: Transcription factor IRF5 promotes a pro-inflammatory response in macrophages leading to vulnerable plaque formation and plaque destabilization, providing genetic evidence for targeting macrophage polarization in atherosclerosis. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): DFG